Lymphocyte subpopulations and surface membrane immunoglobulins in myasthenia gravis. Issue 2 (February 1982) - Landi, G; Galli, M; Ciboddo, G; Colombo, G; Scarlato, G
Abstract : Lymphocyte subpopulations were studied in 16 myasthenic patients by means of E and EA7s rosettes and surface membrane immunofluorescence. Myasthenic patients showed an increase in lymphocytes with surface IgM an IgD when compared to a control group. In female patients this increase was highly significant, and lymphocytes bearing membrane IgG and IgA were also augmented. No difference was found in male patients when compared with sex-matched controls. These results suggest an activation of the B cell compartment restricted to female patients, and support the hypothesis of different immunopathogenetic mechanisms in this disease.